Psychosocial Risk Factors and the Association With Carpal Tunnel Syndrome: A Systematic Review. (September 2018) - Mansfield, Michael; Thacker, Michael; Sandford, Fiona
Background: Carpal tunnel syndrome (CTS) is the most common entrapment neuropathy of the upper limb. Research has shown that associative factors for CTS include occupational and biomechanical elements, sex, and age. To date, no systematic review has been undertaken to determine specifically whether there are any psychosocial risk factors in developing CTS. The objective is to determine whether psychosocial factors are associated with and/or predict the development of CTS.Methods: A systematic review was conducted including searches of PubMed (MEDLINE), EMBASE, and CINAHL from inception to May 30, 2017. Quantitative studies must have investigated a minimum of 1 or more psychosocial factors—cognitive, affective, behavioral, vocational, or interpersonal processes (eg, social support)—and include a point or risk estimate. One reviewer conducted the search and 2 reviewers independently assessed eligibility and completed methodological quality assessment using a modified Downs and Black checklist. Data were analyzed narratively.Results: Six moderate- to high-quality studies were included in the final review. Five studies reported a positive association between psychosocial factors and CTS, where psychosocial factors were more in those who reported CTS. One study reported no positive or negative association with CTS development. Four studies reported a negative association between psychosocial factors and CTS, where psychosocial factors were less in those who reported CTS.Conclusions: There is limited evidence for a positive association between psychosocial factors and CTS. However, this was not a consistent finding across all included studies. Further research is indicated in standardizing CTS diagnostic criteria and investigating other working environments.